Assessment of the imperative features of an l-arginine 4-nitrophenolate 4-nitrophenol dihydrate single crystal for non linear optical applications. (3rd January 2017) - Sonia; Vijayan, N.; Vij, Mahak; Kumar, Prashant; Singh, Budhendra; Das, Subhasis; Rajnikant; H., Soumya
Abstract : A good quality single crystal was grown by adopting a slow evaporation solution growth technique. The optical, thermal and mechanical properties of the title compound were examined to determine its suitability for device fabrication. Abstract : Anl -arginine 4-nitrophenolate 4-nitrophenol dihydrate (LAPP) single crystal has been grown by adopting a slow evaporation solution growth technique (SEST). The crystal structure and its lattice dimensions along with the space group were confirmed through single crystal X-ray diffraction and it was found that the crystal belongs to a monoclinic crystal system with the space group P 21 . Using Hall–Williamson's equation, the strain present in the single crystal was ascertained. The functional groups of the title compound were identified using heteronuclear correlation methods (HETCOR) and Raman spectroscopy. The optical parameters of the grown single crystal were evaluated using UV-vis-NIR analysis. Thermal parameters like the specific heat, thermal effusivity, thermal diffusivity and conductivity of the LAPP single crystal were computed from the photopyroelectric effect. Furthermore, mechanical stability parameters like the hardness, stiffness and Young's modulus were examined using a nanoindentation technique. The ferroelectric behavior and laser damage threshold were also assessed.